An inhibitory carboxyl-terminal domain in Ets-1 and Ets-2 mediates differential binding of ETS family factors to promoter sequences of the mb-1 gene. - Hagman, J (1992)
The mb-1 gene is expressed only during the early stages of B-lymphocyte differentiation. Here we show that the mb-1 proximal promoter region contains a functionally important binding site for members of the ETS family of DNA-binding proteins. We found that both the E26 virus-encoded v-ets and the myeloid/B-cell-specific factor PU.1 bind efficiently to this site in vitro. By contrast, Ets-1, the lymphocyte-specific cellular homologue of v-ets, and the related, more ubiquitously expressed Ets-2 protein interacted weakly with this binding site. DNA binding by both Ets-1 and Ets-2, however, could be increased 20- to 50-fold by deleting as few as 16 carboxyl-terminal amino acids. The inhibitory carboxyl-terminal amino acid sequence is highly conserved between Ets-1 and Ets-2 but is not present in either v-ets or PU.1. Replacement of the carboxyl-terminal amino acids of v-ets with those of Ets-1 decreased DNA binding by v-ets drastically. Cotranslation of Ets-1 transcripts encoding proteins of different lengths suggested that Ets-1 binds DNA as a monomer. Therefore, the carboxyl-terminal inhibitory domain appears to interfere directly with DNA binding and not with homodimerization. Finally, the functional relevance of ETS factor binding to the mb-1 promoter site was evidenced by the stimulation of transcription through this site by a v-myb-v-ets fusion protein. Together, these data suggest that one or more ETS family factors are involved in the regulation of mb-1 gene expression.